Same as it ever was: Comparing young adults' age bias toward older workers from 1989 and 2015 - Petery, Gigi; Barnes-Farrell, J. (2018)
Age biased attitudes and behaviours towards older workers are well documented. Although both positive and negative older worker stereotypes exist, negative beliefs tend to exert greater influence on perceptions about older workers. This negative bias persists, despite research that empirically discredits negative and supports positive older worker stereotypes Bias from negative stereotypes is problematic because the population is ageing globally, resulting in sharp increases in participation rates of workers age 55 and older within Australia and most other developed nations continuing for the foreseeable future. At the same time, the increased participation of older workers has provided greater opportunities for older workers to be evaluated based on their merit, rather than through stereotyped beliefs. As a result, we expected contemporary endorsements of negative stereotypes to be weaker and of positive stereotypes to be stronger compared to those of the past. To explore this hypothesis, data from two separate, but similar, groups of students from the same university, one collected in 1989 and the other in 2015, were examined. Unexpectedly, students in 2015 expressed a stronger negative bias about older workers compared to students in 1989. However, increased variability in some of the responses from the 2015 sample implies a degradation in the uniformity of agreement in those stereotypic beliefs. Furthermore, and in line with intergroup contact theory, in both samples positive work experience with older workers was associated with more positive attitudes towards older workers in general. These finds suggest that organisations can aid in reducing negative age bias by creating intergenerational work groups that provide ample opportunities for cross-generational interactions and collaboration.